Whiteness and national identity: teacher discourses in Australian primary schools. Issue 1 (2nd January 2018) - Walton, Jessica; Priest, Naomi; Kowal, Emma; White, Fiona; Fox, Brandi; Paradies, Yin
Abstract: The study examines how white teachers talked to children about national identity and cultural diversity by drawing on qualitative research with eight- to 12-year-old students and their teachers from four Australian primary schools with different racial, ethnic and cultural demographics. Despite a range of explicit and implicit approaches that fostered different levels of critique among students, teachers often communicated Australian national identity as commensurate to white racial and Anglo-Australian cultural identity. We identified three main approaches teachers used to talk about national identity and cultural diversity: cultural essentialism, race elision and a quasi-critical approach. We conclude that the wider education system needs to develop a more formal curriculum structure that guides teachers in developing a better awareness of the power of white normativity, and to critically and explicitly counter discourse and practice that centres whiteness as foundational to dominant conceptualisations of national identity.